W.C. Fields from the Ziegfeld Follies and Broadway Stage to the Screen Becoming a Character Comedian - Wertheim, Arthur Frank; SpringerLink (Online service) (New York : Palgrave Macmillan US(Imprint), 2016)
This book reveals how Fields became a character comedian while performing in Broadway's most illustrious revue, the Ziegfeld Follies. As the first biography to use the recently opened Fields Papers at the Motion Picture Academy, the book explores how Fields years as a Follies entertainer portraying a beleaguered husband and a captivating conman became a landmark turning point in his career, leading to his fame as a masterful film comedian. The book also untangles a web of mysteries about Fields's turbulent private life, from the heartrending stories about the tragic relationship with his calculating wife who refused to divorce him, to his estranged son controlled by his mother, to the seven-year extra-marital affair with a chorus girl that led to the birth of an unwanted child. This electrifying saga illuminates a complex dual personality, whirling from tenderness to brusqueness, who endured so much anguish in order to bring the gift of laughter to millions. Although vilified by Ziegfeld and assailed by demons, Fields survived the cutthroat rigors of Broadway show biz to become a legendary American iconoclast and cultural icon.
Introduction -- Prologue. Becoming a Character Comedian -- Part I. 1915 - A Momentous Year -- 1. Confronting Florenz Ziegfeld -- 2. Pool Sharks and His Lordship's Dilemma -- Part II. The Beleagered Sportsman -- 3. Spoofing Croquet -- 4. Lampooning Tennis -- 5. The Frustrated Duffer -- Part III. Entr'actes -- 6. The Three Musketeers -- 7. Bessie and Hattie -- 8. Fields's Well Never Went Dry -- 9. From the Midnight Frolic to the Front Lines -- Part IV. Lampooning the Dysfuntional Family -- 10. The Flivertons -- 11. The Breakup with Ziegfeld -- Part V. Broadway Stardom -- 12. Oh, what a Scandal! -- 13. "Confidence Man of the Ages" -- 14. Two Legendary Iconolasts Converge -- 15. The Comic Supplement -- 16. A Follies Farewell -- Epilogue. Fields Encounters D. W. Griffith -- Appendix. The Ziegfeld Mystique.
Keywords: Theater-History.; Motion pictures-History.